The world market of high technologies: features and prospects of development - K. A. Turkeeva; G. Kh. Umarova (Экономика: стратегия и практика)
The article discusses the features of the development of the world market of high technologies. High technologies are the newest and most advanced technologies of our time, which are the most important link of the scientific and technical revolution (STD) at the present stage. The article analyzes the development of the technology market in developed and developing countries at the present stage, namely, the United States, the European Union, China and Kazakhstan. The article assesses the dynamics of the high-tech market development and defines the role of the high-tech products market in the system of modern international economic relations. The positions of the rating of individual countries in the technology market are studied. Special attention is paid to the position of some countries in the world market of industry 4.0 technologies. As a result, the trends in the development of the global high-tech market are justified, which allows us to determine the place of Kazakhstan among other countries.The relevance of this topic is not in doubt, since the development of high technologies is one of the most important activities of the enterprise and an important indicator of the state of the country’s economy.